নারী প্রতিনিধিত্ব ও রাজনীতি - গুহঠাকুরতা, মেঘনা; বেগম, সুরাইয়া; আহমেদ, হাসিনা (Samāja nirīkshaṇa saṃkalana ;)
On the representation and role of women in society and politics, study with respect to Bangladesh; contributed articles.